2001
DOI: 10.1038/sj.thj.6200133
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α release is a major biological event associated with rituximab treatment

Abstract: This analysis demonstrates that rituximab infusion was rapidly followed by activation of complement, B-lymphocyte cytolysis, and TNF-alpha release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 12 publications
0
47
1
2
Order By: Relevance
“…Complement activation and cytokine secretion, in particular, seems to be the causative factors in side effects associated with infusion reactions [14]. Studies have found complement (C3b/c and C4b/c) and cytokine (TNF-a, IL6, and IL8) levels to be elevated after rituximab infusion [2,[14][15][16]. In particular, TNF-a has been postulated as the main component in the pathogenesis of ILD because of its proinflammatory effects by inducing chemokines, inflammatory mediators, and angiogenic factors [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complement activation and cytokine secretion, in particular, seems to be the causative factors in side effects associated with infusion reactions [14]. Studies have found complement (C3b/c and C4b/c) and cytokine (TNF-a, IL6, and IL8) levels to be elevated after rituximab infusion [2,[14][15][16]. In particular, TNF-a has been postulated as the main component in the pathogenesis of ILD because of its proinflammatory effects by inducing chemokines, inflammatory mediators, and angiogenic factors [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is now considered part of the standard therapy for CD201 NHL and has been used for autoimmune disorders such as idiopathic thrombocytopenic purpura, systemic lupus erythematous, and autoimmune hemolytic anemia [1]. The most common side effects are infusion related and include fever, chills, and rigors [2]. Respiratory complications can include cough, rhinitis, brochospasm, dyspnea, and sinusitis.…”
Section: Introductionmentioning
confidence: 99%
“…However, CDC seems to be the most important mechanism of cell lysis in chronic lymphocytic leukemia (CLL) patients (Kennedy et al, 2004). CDC is probably involved in the cytokine-release syndrome and its toxicity (Bienvenu et al, 2001).…”
Section: Mechanisms Of Action Of Rituximabmentioning
confidence: 99%
“…Mechanisms leading to late-onset ILD remain unclear. A potential explanation may be the induction and release of cytokines following rituximab binding to CD20 + cells [2,4]. Because the patient was treated concomitantly with cytotoxic drugs, we recognise that it is difficult to completely rule out cytotoxic FIGURE 1 Chest computed tomography scan revealing diffused micronodules over bilateral lung field.…”
mentioning
confidence: 99%